Teen Finance - GREGÓRI, Erick Junior; ANDRADE, João Vitor Meloni; FARIAS, Matheus Euphrasio Barreira Paim; RIBEIRO, Pedro Henrique de Carvalho; TEIXEIRA, Vinicius Monteiro Ribeiro; SANTOS, Yuri Gabriel Lopes dos (044, 2024)
Uma pesquisa detalhada foi conduzida, através da distribuição de questionários em redes sociais, a fim de compreender os hábitos financeiros e as principais dificuldades de gestão do dinheiro enfrentadas pelo público-alvo. Os resultados dessa análise destacaram a necessidade premente de integrar a educação financeira desde cedo, demonstrando que muitos jovens carecem de conhecimento básico sobre dinheiro e têm dificuldades em lidar com questões como investimentos e poupança. Devido à crescente complexidade da gestão financeira e à necessidade de um controle financeiro mais eficaz, nosso projeto consiste no desenvolvimento de um site focado em fornecer uma solução acessível e útil para ajudar as pessoas no gerenciamento de suas finanças pessoais. O site será uma plataforma abrangente, oferecendo conteúdo educativo de fácil compreensão sobre diversos temas, como investimentos, poupança e controle de gastos. Utilizando recursos como podcasts, vídeos e apostilas, a plataforma permitirá que os usuários aprendam e aprimorem suas habilidades financeiras de forma gradual, conforme suas necessidades. O objetivo é proporcionar um ambiente que ajude os indivíduos a se tornarem mais conscientes e capacitados financeiramente. Por meio de recursos como podcasts, vídeos e apostilas, o site visa estabelecer um ambiente educacional que permita aos usuários aprender e aprimorar suas habilidades financeiras gradualmente, de acordo com suas necessidades individuais. O desenvolvimento do projeto foi cuidadosamente planejado em várias etapas, iniciando com a definição do público-alvo, com foco especial nos adolescentes do ensino médio, uma fase crucial de preparação para a vida adulta.

A detailed survey was conducted, distributing questionnaires on social media to understand the financial habits and main money management challenges faced by the target audience. The results of this analysis highlighted the urgent need to integrate financial education from na early age, demonstrating that many young people lack basic knowledge about money and struggle with issues like investments and savings. Due to the increasing complexity of financial management and the increasing need for financial control, our website’s main goal is to offer na accessible and useful solution to help people manage their personal finances. Aspects of personal finances, such as investments, savings and expense control. Through resources such as podcasts, videos and handouts, the site aims to establish na educational environment that allows users to learn and improve their financial skills gradually, according to their individual needs. The development of the project was carefully planned in several stages, starting with defining the target audience, with a special focus on high school teenagers, a crucial phase of preparation for adult life

This article discusses the implementation and benefits of the digital registration system for attendance control at State Technical Schools (ETECs). Traditionally, controlling student attendance has been a challenging task for educational institutions, often relying on manual and error-prone methods. However, the introduction of digital registration systems represents a modern and effective solution to this issue. This article examines how the digital registration system works as a time clock, capturing precise information about student entry and exit. The system records data such as the student's registration number (RM), name, and entry and exit times, providing a comprehensive view of student attendance over time.
Teen Finance
Keywords: Web sites; Sistemas de controle-automação; Informação e Comunicação